Comparison of Chest Radiographic Views in Patients with Smear Positive and Smear Negative Pulmonary Tuberculosis - Behrooz Ataei; Atoosa Adibi; Abbasali Javadi; Farzin Khorvash; Parisa Farzanefar; Nazila Kasaeian (مجله دانشکده پزشکی اصفهان, 2011)
• Background: The present study aimed to determine and compare the frequency distribution of chest radiographic views in patients with smear positive and smear negative pulmonary tuberculosis (TB). • Methods: In this cross-sectional study, 142 files of patients with smear positive and smear negative pulmonary tuberculosis were carried-out. We evaluated the demographic data, sputum acid-fast staining result and chest radiography of patients and recorded the results involving the region and the type of the lung involvement. Then, the collected data were analyzed. • Finding: The mean age of the patients was 46.46 ± 20.51; 60 patients (42.3%) were men and 82 (57.7%) were women. In addition, 53 patients (37.3%) were Iranian and 89 (62.7%) were Afghani. From 142 patients, 81 (57%) were smear positive and 61 (43%) were smear negative. The mean age (P = 0.51), sex distribution (χ2 = 1.68; P = 0.2) and the nationality distribution (χ2 = 0.38; P = 0.38) were not different between smear positive and smear negative patients. There was not any significant difference between the region (χ2 = 0.94; P = 0.8) and the type (χ2 = 12.88; P = 0.12) of the lung involvement, too. • Conclusion: Based on the results of this study, there was no difference between smear positive and smear negative patients in terms of chest radiography findings.